2021
DOI: 10.1186/s12905-020-01149-5
|View full text |Cite
|
Sign up to set email alerts
|

Period poverty and mental health implications among college-aged women in the United States

Abstract: Background The purpose of this study is to examine the frequency of “period poverty,” or not being able to afford sanitary products, among university students, and associations with poor mental health. Methods An online survey was conducted with a nationally-drawn sample (N = 471) of college-attending women to assess the association between period poverty and depression. Period poverty was measured via two questions designed for this study; depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 17 publications
3
49
0
10
Order By: Relevance
“…While inadequate attention has been directed toward the menstrual experiences of students in the United States of America (U.S.A.) (12,13), a growing body of evidence has begun to document some of the challenges faced by menstruating girls and young women in schools (8,(14)(15)(16). For example, many adolescent girls, especially those from poor socioeconomic backgrounds, lack adequate menstruation education (8,14,(17)(18)(19) and struggle to afford basic period products (15,16,20,21). A survey conducted with 58 female high school students in St. Louis, Missouri found that nearly half had been unable to afford needed menstrual products at least once in the last school year (16).…”
Section: Introductionmentioning
confidence: 99%
“…While inadequate attention has been directed toward the menstrual experiences of students in the United States of America (U.S.A.) (12,13), a growing body of evidence has begun to document some of the challenges faced by menstruating girls and young women in schools (8,(14)(15)(16). For example, many adolescent girls, especially those from poor socioeconomic backgrounds, lack adequate menstruation education (8,14,(17)(18)(19) and struggle to afford basic period products (15,16,20,21). A survey conducted with 58 female high school students in St. Louis, Missouri found that nearly half had been unable to afford needed menstrual products at least once in the last school year (16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have shown that about 65% of women who are undergoing or have completed treatment for BPD reported significant mood changes across the MC, and 59% of them, including those taking oral contraceptives, reported longer MCs (18).…”
Section: Bipolar Disorder (Bpd)mentioning
confidence: 98%
“…The stigma that shrouds periods further prevents individuals from talking about it. 2,4 NEED FOR RESEARCH AND ENGAGEMENT Lack of data and limited research on period poverty is a challenge. 2 More research and engagement are called for.…”
Section: What Then Is Period Poverty?mentioning
confidence: 99%
“…There are social, cultural, economic, and political barriers to menstrual products, education, and sanitation. 2,5 Period poverty has also been associated with health issues including depression 4 and urinary tract infections. 2…”
Section: Barriers To Menstrual Products Education and Sanitationmentioning
confidence: 99%